2007
DOI: 10.1017/s135561770808003x
|View full text |Cite
|
Sign up to set email alerts
|

A demonstration of endogenous modulation of unilateral spatial neglect: The impact of apparent time-pressure on spatial bias

Abstract: Unilateral neglect, a lack of awareness for one side of space, is a common and debilitating consequence of stroke. Previous work has identified a relationship between enduring left neglect and diminished general alertness and shown that increasing alertness can temporarily reduce the severity of the spatial bias. In that research, alertness was modulated by loud tones or with pharmacological stimulants. Here we examine whether cognitive, endogenously driven changes can produce similar short-term improvements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This would be consistent with both the normal and clinical literature on lateralised shifts with low alertness and distraction15161720212228 and studies showing disengagement of prefrontal and parietal regions345 with consequent reduction in cognitive control and target detection29. The magnitude and reliability of the rightward shift reported here suggests a tractable method for examining this directionally specific effect, including its relationship with hemispheric specialisation in other functions such as language.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This would be consistent with both the normal and clinical literature on lateralised shifts with low alertness and distraction15161720212228 and studies showing disengagement of prefrontal and parietal regions345 with consequent reduction in cognitive control and target detection29. The magnitude and reliability of the rightward shift reported here suggests a tractable method for examining this directionally specific effect, including its relationship with hemispheric specialisation in other functions such as language.…”
Section: Discussionsupporting
confidence: 89%
“…There may be a number of reasons for this including right-hemisphere dominance in aspects of spatial cognition and attention (making it more able to compensate for left hemisphere damage than vice versa12) and prolongation of neglect by co-occurring deficits in alertness, themselves associated with right hemisphere function1314. The latter argument has been supported by temporary amelioration in rightward bias that follows exposure to stimulating noises, thoughts or medication151617.…”
mentioning
confidence: 99%
“…When the time restrictions and feedback were removed, prism adaptation resulted in improvements on standard neglect measures. However, in another study, a time-pressure component showed a positive effect on a spatial cancellation task [31]. Specifically, in this study the participants were asked to complete a spatial cancellation task with and without instructions regarding a time limit.…”
Section: Neglectmentioning
confidence: 99%
“…Patient data from both our group (Duncan et al, 1999;Peers et al, 2005) and others (Habekost & Rostrup, 2006;Corbetta & Shulman, 2002;Robertson et al, 1997a) indicate that pathological spatial biases tend to arise and persist in the context of more general attentional impairment. Interventions that manipulate general attentional resources, for example increasing alertness via stimulants or stimulation (George, Mercer, Walker, & Manly, 2008;Gorgoraptis et al, 2012) or reducing alertness with sleep onset (Bareham, Manly, Pustovaya, Scott, & Bekinschtein, 2014), have been shown to phasically modulate spatial bias, suggesting rather direct interactions between these components. Despite not explicitly targeting spatial bias, therefore, it may be possible to improve spatial functions by focussing on other aspects of attention.…”
Section: Introductionmentioning
confidence: 99%